Community Based Tourism dalam Upaya Pengembangan Objek Wisata Ceking Terrace Desa Tegallalang Kabupaten Gianyar - Sulasmi, Ni Kadek; Winaya, I Ketut; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2021)
Tegallalang village has officially managed Ceking Terrace tourism object through Badan Pengelola Objek Wisata Ceking and is corroborated Bendesa Tegallalang Regulation Number: 055/VI/DPT/2011 on the arrangement of Ceking area. This research applies descriptive qualitative method and observation, interview, and documentation as the method of collecting the data. The purpose of this research is to know how local people participate in the development of ceking terrace tourism object Tegallalang Village Gianyar Regency applying tourism development theory and Comunity Based Tourism approach according to bambang sunaryo through 3 indicators which influence the application of Comunity Based Tourism namely planning stage, implementation stage, and monitoring and evaluation stage. The result of this research is the development of the Ceking Terrace through planning and evaluating, however, it was not maximal in the implementation process. It is mostly caused by the problem in the human source and the financial resource. Keywords: Community Based Tourism, Community Partisipation, Ceking Terrace